(untitled) - Stempleski, Susan (Boston, MA., 2006)
To help students expand their fluency, World Pass focuses on dynamic vocabulary building, essential grammar, and stimulating listening, speaking, reading, and writing activities that emphasize the language they need for real world communication.
Keywords: English language; Study and teaching,Foreign speakers